PENGARUH MOTIVASI KERJA DAN KECERDASAN EMOSIONAL TERHADAP PRODUKTIVITAS KERJA - Fransiska, Arina (PRODU: Prokurasi Edukasi Jurnal Manajemen Pendidikan Islam, 2019)
This study aims to prove empirically the effect of work motivation and emotional intelligence on work productivity. This study used a sample of 66 employees of PT MNC Sky Vision KPP Padang with a proportionate stratified random sampling technique. The data used are primary data obtained through distributing questionnaires to selected employees. This study has two categories of variables. The first is the independent variable, namely work motivation and emotional intelligence. The two dependent variables are work productivity. The analysis method used is descriptive and quantitative analysis. The results of testing the first hypothesis found that work motivation has a significant effect on the work productivity of employees of PT MNC Sky Vision KPP Padang. The results of testing the second hypothesis found that emotional intelligence has a significant effect on the work productivity of PT MNC Sky Vision KPP Padang employees. The results of the third hypothesis found that work motivation and emotional intelligence together have a significant effect on the work productivity of PT MNC Sky Vision KPP Padang employees.